Strategic design and innovative thinking in business operations the role of business culture and risk management preface - Dinçer, Hasan; Hacıoğlu, Ümit; Yüksel, Serhat (Springer, 2018)
[Abstract Not Available]
WOS: 000444687500001
Keywords: Innovative Thinking; Business Operations; Business Culture